2020
DOI: 10.1080/09540105.2020.1807916
|View full text |Cite
|
Sign up to set email alerts
|

A novel biomimetic immunoassay method based on Pt nanozyme and molecularly imprinted polymer for the detection of histamine in foods

Abstract: This study used surface imprinting polymerization to synthesize molecularly imprinted polymer on the surface of PAF-45 material (PAF-45@MIP). SEM, FT-IR, static and kinetic adsorption experiments were adopted to investigate the morphology and properties of the MIP. The results showed that the PAF-45@MIP could rapidly absorb histamine with a high adsorption capacity. Using PAF-45@MIP as a biomimetic antibody and Pt nanozyme as a marker, a novel direct competitive biomimetic immunoassay (BIA) method for rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This ideal combination was further improved by preparing MIP films for selective recognition and reusability, allowing to develop assays whose results were comparable to those obtained by HPLC [ 94 , 95 ]. Other configurations have been proposed, such as the use of Pt@SiO 2 NPs and a MIP for highly sensitive and selective detection of histamine with a limit of detection of 0.128 mg L −1 [ 96 ].…”
Section: Nanozymes@mipsmentioning
confidence: 99%
“…This ideal combination was further improved by preparing MIP films for selective recognition and reusability, allowing to develop assays whose results were comparable to those obtained by HPLC [ 94 , 95 ]. Other configurations have been proposed, such as the use of Pt@SiO 2 NPs and a MIP for highly sensitive and selective detection of histamine with a limit of detection of 0.128 mg L −1 [ 96 ].…”
Section: Nanozymes@mipsmentioning
confidence: 99%
“…In recent years, many new ELISA technologies based on biomimetic antibody and nanozyme have been reported (He et al, 2020;Wang et al, 2020). Molecularly imprinted polymers (MIPs) are man-made functionalized materials, which have specific recognition ability toward the template molecules (Teixeira et al, 2021;Trevizan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with biology antibodies, MIPs have many advantages to be used as artificial antibody in the ELISA method due to their excellent properties of high selectivity, simple fabrication, good stability and reusability (Lata et al, 2015;Li et al, 2017;Wulff, 1995;Ye & Mosbach, 2008;Yu et al, 2020). Nanozymes are functional nanomaterials with enzyme-like characteristics, which can be used in ELISA because of their adjustable enzyme-like catalytic activity, simple preparation, low cost and high stability (He et al, 2020;Huang et al, 2019;Wang et al, 2020;Wu et al, 2019Wu et al, , 2020Zhou et al, 2017). Ataee-Esfahani and co-workers suggested that the Au@Pt nanomaterial could act as a potential peroxidase mimetics, which can oxidize substrate tetramethylbenzidine (Ataee-Esfahani et al, 2010).…”
Section: Introductionmentioning
confidence: 99%